The Effectiveness of Gallery Walk Strategy to Students’ Writing Skill - Nantang, Basir (Al-Iftah: Journal of Islamic studies and society, 2023)
This research is aimed to get empirical evidence on the effect of gallery walk technique on students’ writing skillt eleventh Grade of SMA Muhammadiyah Kalosi Kabupaten Enrekang in Academic Year 2022/2023. This research used quantitative method and the research design used is a quasi-experimental design. The population of this research is all eleventh Grade students of SMA Muhammadiyah Kalosi Kabupaten Enrekang. The sample technique used purposive sampling that consist of 60 students. The samples are assigned into two groups: class VII-2 as an experimental class and VII-3 as a control class and each class consist of 30 students. The instrument of this research was written test. The result of this research was obtained from calculating the data using t-test with the significance level (α) = 0.05 and also calculated the effect size. The result showed that the mean score of post-test in experimental class is higher than control class (79>65.73). Therefore, statistic hypothesis test showed that ρ-value of post-test and gained score is 0.000 < sig. α = 0.05. Also, the effect size of this result is 1.53. It proved that the alternatives hypothesis (H a ) is accepted and the null hypothesis (H ) is rejected. To sum up, gallery walk technique is effective with strong level on students’ writing skill.